Alcohol use, pregnancy and associated risk factors: a pilot cross-sectional study of pregnant women attending prenatal care in an urban city - Imelda K. Moise (BMC, 2019)
Abstract Background Alcohol consumption during pregnancy is associated with adverse pregnancy outcomes such as preventable alcohol-related developmental disability fetal alcohol syndrome. In Zambia, alcohol use and associated risk factors have not been investigated, and screening in prenatal care is nonexistent. This study determined individual correlates and the prevalence of alcohol use in pregnant women attending prenatal care at two health clinics in Lusaka, Zambia. Methods A study adopted a cross-sectional design and recruited 188 pregnant women after seeking their informed consent from July 19 to 31, 2017. Participants aged 18 or over completed the T-ACE (Tolerance, Annoyance, Cut Down and Eye Opener) screening tool and validated alcohol-screening questionnaires on self-reported alcohol use periconceptional and during conception period while at their regular prenatal visit. The T-ACE screening tool assessed the risk of alcohol dependence in four short questions. The questionnaires included demographic questions. Bivariate analyses were performed using the χ2 test for dichotomous variables and the t-test for continuous variables. Mixed-effects linear models were used to evaluate the effect of outcome variables with patient-level variables. Results About 40 (21.2%) pregnant women were identified by the T-ACE as at-risk for problem drinking during pregnancy. Except for regular prenatal care and distance, there was no difference in the demographic factors between pregnant women who scored < 2 on the T-ACE and those that scored > 2 points (all p's > 0.05). A small proportional of women at both clinics reported binge drinking during the periconceptional period (12.7% vs. 3.2%, p = 0.003) and beyond periconception period. Excluding employed women, no significant relationships were observed between alcohol use and demographic factors. Conclusion Alcohol consumption is prevalent in the periconceptional period and during pregnancy in pregnant women attending prenatal care in Zambia. Findings underscore the need for targeted alcohol use screening and intervention for pregnant women.